Towards increasing forages options and registration in Tanzania - Mwendia, Solomon; Nzogeal, Beatus; Kizima, Jonas; Lukuyu, Ben A.; Peters, Michael (International Center for Tropical Agriculture, 2023)
Compared to food crops, forages registration in Tanzania has lagged. Largely, the system relies on old materials e.g. Chloris gayana developed decades ago without no newer officially registered materials in the country to benefit livestock production especially cattle. This shortcoming has been recognized before, but no concerted effort towards addressing the same. Under the CGIAR Sustainable Animal Productivity (SAP) initiative, efforts are underway to address the concern starting with selected forage hybrids with good chance of being registered. Registration would contribute to improving forage seed system in the country by allowing private sector engagement to increase seed access more sustainably. Additionally, more forage materials are under testing in different locations in Tanzania.